2007
DOI: 10.1167/7.10.16
|View full text |Cite
|
Sign up to set email alerts
|

The shape of the human lens nucleus with accommodation

Abstract: Knowledge about geometric properties such as shape and volume and Poisson's ratio of the nucleus can be used in the mechanical and optical modeling of the accommodation process. Therefore, Scheimpflug imaging was used to determine the shape of the human lens nucleus during accommodation in five subjects. To describe the shape of the nucleus, we fitted a parametric model of the cross-sectional geometry to the gradient of the Scheimpflug images using the Hough transform. The geometric model made it possible to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 26 publications
6
56
0
Order By: Relevance
“…The radius of curvature was 6.98mm for the anterior and 5.62mm for the posterior lens capsule. These were consistent with measurements of an accommodated lens (Rosen et al 2006;Hermans et al 2007Hermans et al , 2009Kasthurirangan et al 2011;Lanchares et al 2012). The geometry obtained using a pressure of 5-6mmHg had slightly greater thickness, but the dimensions were still within the range of measurements and human models (Augusteyn et al 2011).…”
Section: Resultssupporting
confidence: 83%
“…The radius of curvature was 6.98mm for the anterior and 5.62mm for the posterior lens capsule. These were consistent with measurements of an accommodated lens (Rosen et al 2006;Hermans et al 2007Hermans et al , 2009Kasthurirangan et al 2011;Lanchares et al 2012). The geometry obtained using a pressure of 5-6mmHg had slightly greater thickness, but the dimensions were still within the range of measurements and human models (Augusteyn et al 2011).…”
Section: Resultssupporting
confidence: 83%
“…This was in contrast with a report using MRI, 26 which suggested a decrease of this parameter (only significant in the meridional direction), and a 50% contribution of the lens thickness nucleus to the change of lens thickness with accommodation. Studies based on Scheimpflug imaging revealed a much higher contribution of the lens nucleus (90%) in humans 6,64,65 and rhesus monkey. 66 While differences arising from the definition of the lens nucleus and the data analysis are expected, our study on cynomolgus monkeys also supports a large contribution of the lens nucleus in thickness changes (69%, following the definition proposed by Kasthurirangan et al 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The shape of the contours used in the model are regular and follow the surface shape; in the living lens there is a deviation from regularity in the central contours ( Fig. 6B and C); (Rosales et al, 2006;Hermans et al, 2007) and the lens has been found to have rounder lamellae in the central regions with the outer lamellae taking on a more lenticular shape (Brown et al, 1988).…”
Section: Discussionmentioning
confidence: 92%
“…2(A) to simulate the lens shape in vivo. (Rosales et al, 2006) and (C) a 28 year old lens (Hermans et al, 2007). The image in (B) was taken of the unaccommodated lens; the accommodative state of the image in (C) was not given but the shape suggests it is not accommodated or in a minimal state of accommodation.…”
Section: Discussionmentioning
confidence: 99%